The implication of Trans-Pacific Partnership (TPP) towards Small Medium Enterprises (SMES) internationalization / Ahmad Aizuddin Ahmad Rosli and Suliahanis Nasuha - Ahmad Rosli, Ahmad Aizuddin; Nasuha, Suliahanis (Faculty of Business and Management, 2014)
This paper aims to identify the impact of free trade agreement towards SME internationalization. There are three main factors that significantly impact the SME internationalization which is the government procurement, intellectual properties and market access. Significantly Malaysia had signed numerous regional and bilateral agreements since 1992. TPP agreement deems to be the most ambitious that Malaysia had ever merged in. Malaysia recently indicates their mission that keen to sign the agreement although many complaints had being voice out. In Malaysia, despite having a significant contribution to the economy, SMEs also contributed to the economy as well as increased the national revenue. Thus, the questioned arise as SME inquire the impact that they will face upon appliance of TPP being implemented. Thus, this paper explores how this is reflected in the reaction of TPP agreement by a sample size of SME that specialized in food and beverages industry